Loss of T-cadherin (CDH-13) regulates AKT signaling and desensitizes cells to apoptosis in melanoma - Bosserhoff, Anja K.; Ellmann, Lisa; Quast, Annika S.; Eberle, Juergen; Boyle, Glen M.; Kuphal, Silke (Molecular Carcinogenesis, 2014)
An understanding of signaling pathways is a basic requirement for the treatment of melanoma. Currently, kinases are at the center of melanoma therapies. According to our research, additional alternative molecules are equally important for development of melanoma. In this regard, cancer progression is, among other factors, driven by an altered adhesion via cadherins. For instance, the de-regulated expression of the adhesion molecule T-cadherin is found in various cancer types, including melanoma, and influences migration and invasion. T-cadherin is thought to affect cellular function largely through its signaling and not its adhesion properties because the molecule is anchored into the cell membrane by a glycosylphosphatidylinositol (GPI) moiety. However, detailed knowledge about the consequences of the loss of T-cadherin in melanoma is currently lacking. For this reason, we were interested in assessing which signaling pathways are initiated by T-cadherin. The tumor growth of subcutaneously injected T-cadherin-positive melanoma cells was diminished compared with T-cadherin-negative cells in nude mice. The difference in tumor volume was not due to decreased proliferation but rather due to increased apoptosis. After the expression of T-cadherin was induced, we detected V-AKT murine thymoma viral oncogene homolog (AKT) and FoxO3a hypophosphorylation accompanied by the downregulation of the antiapoptotic molecules BCL-2, BCL-x and Clusterin. Furthermore, we detected a diminished transcriptional activity of CREB and AP-1. We demonstrated that T-cadherin functions as a pro-apoptotic tumor suppressor that antagonizes AKT/CREB/AP-1/FoxO3a signaling, whereas NFκB, TCF/LEF and mTOR are not part of the T-cadherin signaling pathway. Notably, we found that the restoration of T-cadherin in melanoma cells causes sensitization to apoptosis induced by CD95/Fas antibody CH-11. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: AKT; AP-1; Cell adhesion; CREB; FoxO3a